Heat-Resistant Foam Concrete on the Basis of Two-Component Binder - S. N. Leonovich; D. V. Sviridov; A. L. Belanovich; V. P. Savenko; S. A. Karpushenkov (Наука и техника)
The composition of dry mix on the basis of two-component cementing agent (aluminous cement and clay of the “Kustikha” field), mineral additives (a metakaolin, the RSAM sulfoaluminate modifier, waste of basalt fiber), Ufapore foamer and the accelerating and plasticizing “Citrate-T” additive is developed. When mixing “Citrate-T” additive with water at Water/Solid = 0.45–0.70, the subsequent mechanical binder and hardening of a foam mass heat-resistant foam concretes with a density of 300–650 kg/m3 are formed (depending on Water/Solid value). Foam concretes have strength on compression of 0.2–2.5 MPa before warming up when their initial strength depends on processes of hydration curing of aluminous cement that provides fixation of their porous structure. After annealing at 1000 °C foam concretes have final strength of 0.3–3.2 MPa due to processes of solid-phase agglomeration of clay with other components of dry mix at their heating. Foam concretes after annealing unlike foam concretes on the basis of a Portland cement and aluminous cement have big strength. Introduction of the accelerating and plasticizing “Citrate-T” additive into composition of the dry mix leads to an increase of rheological properties in expanded foam mass and time reduction of its drying and curing. It has been established that an essential role is played by the relation Water/Solid: at increase in the relation Water/Solid (with 0.45 to 0.70) occurs increase in volume of foam mass after a mechanical binder, and also heterogeneity of pores and their sizes increases that leads to reduction of density of foam concretes and strength on compression.